'Colouring' wipes phenomenon: a peculiar skin pigmentation induced by ascorbic acid observed during lockdown. (1st August 2021) - Guglielmo, A.; Virdi, A.; Vincenzi, C.; Zanotti Russo, M.; Sechi, A.; Patrizi, A.; Neri, I.
Summary: During the SARS‐CoV‐2 (COVID‐19) pandemic, an unusual outbreak of yellow–brown pigmentation on the skin of children was reported. Because of the restrictions on movement promulgated during the lockdown, most consultancies were performed using teledermatology. Data concerning personal care products and application of topical substances were collected, which revealed use of the same brand of wipes for all patients. A liquid chromatography–mass spectrometry analysis was performed to compare the components of the wipes before and after the observation of the pigmentation, in order to detect the responsible substance. This analysis revealed a level about 10‐fold higher than normal of ascorbic acid and its oxidation products (dehydroascorbic acid and L‐threonic acid) in the wipes associated with the pigmentation. These 'colouring wipes' represent a peculiar but harmless phenomenon that highlights the importance of careful questioning about personal care products used by patients.